Dialog z tradycją malarską w literackiej i filmowej twórczości Lecha Majewskiego - Nowakowski, Jacek (Przestrzenie Teorii, 2008)
This article presents Lech Majewski's works in the context of the intersemiotic translation: how the world painting functions in the literature and films of this author. Majewski attempts to make dreams of the modern synthesis of arts come true and in this he reminds of the activities of his Renaissance master, Leonardo da Vinci. This Polish artist by means of the painting tradition (both works as well as fragments of painters' biographies), set in the context of other media (literature, theatre, film) wants to create a modern, intermediate garden of arts whose central topic is the vision of paradise. It can be understood as a place of existence of heroes of his works and - metaphorically - the language of art which the art uses freely uses various materials and media.